KARAKTERISTIK PROTEIN IKAN SEPAT RAWA (Trichopodus thricopterus) ASAL KALIMANTAN SELATAN YANG BERPOTENSI SEBAGAI ANTIDIABETES - Karunita Ika Astuti; Fitriyanti Fitriyanti (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
/KgBB berbeda signifikan dengan kontrol negatif dan tidak berbeda signifikan dengan kelompok glibenklamid yang memiliki persentase penurunan kadar gula sebesar 37,91%. Kata kunci: Antidiabetes, Tepung ikan Sepat Rawa, Kalimantan. ABSTRACT Diabetes treatment using fish is still not much developed. High protein potential in fish as antidiabetic where amino acids such as lysine arginine, leucine, isoleucine and several other amino acids can increase insulin action by increasing energy in the cell metabolism cycle. The purpose of this study is to develop the Kalimantan Sepat Swamp fish as an alternative therapy in patients with diabetes mellitus. Testing the characteristics of protein samples is carried out qualitatively in the form of biuret, ninhydrin, milon, fohl, xantoprotein, and sakhaguchi and testing the antidiabetic potential using test animals in the form of mice and measured levels of mice blood sugar using a glucometer. The treatment group was divided into 5 groups: positive control using Glibenclamide at a dose of 0.5 mg / kgBB, negative control NaCMC, fish meal 100 mg / KgBB; 200 mg / kg, and 300 mg / kg. The results of protein characteristics test showed positive swamp fish meal contained alpha amino acids, tyrosine, amino acids containing sulfur, cyclic, and arginine. In testing the antidiabetic potential of swamp fish meal the results showed that a dose of 300 mg / KgBB was the dose that had the best antidiabetic activity with a percentage decrease of 21.84%, followed by a dose of 200 mg / KgBB of 21.11% and a dose of 100mg / KgBB 6.33%. Antidiabetic activity of swampy fish meal 300 mg / KgBB differ significant with negative control and did not differ significantly from the glibenclamide group which had a decreased percentage of sugar by 37.91%.